Mr Toyin Bawalla Coping Strategies of Today’s Public Secondary School Teachers, Ogun State, Nigeria - Bawalla, Oluwatoyin Gbenga (Dhaulagiri Journal of Sociology and Anthropology, 2020)
The study aimed at investigating the coping strategies adopted by public secondary school teachers in Ogun State, Nigeria. Today, Nigeria’s macro-economic factors ranging from inflation and the inability of the government to reward teachers adequately may have precipitated teachers to engage in other activities for additional income. The study was anchored on Equity Theory propounded by Adams which explains fairness in terms of the treatments of employees in the workplace. The study adopted a qualitative method to elicit information on challenges faced and reasons why teachers moonlight. Key Informant Interviews (KIIs) and In-depth Interviews (IDIs) were conducted for both the ASUSS unions and retired school principals in Ogun State. Data generated were transcribed and content-analyzed. The findings indicated that teachers were dissatisfied with their jobs thereby resorting to other activities which included anchoring events which are popularly known as masters of ceremonies in social events in weddings and coronations. The study recommended that there be a need to increase the pay packages for public secondary school teachers to make the education and teaching profession lucrative in to discourage teachers from moonlighting.